Prospects for radio observations of Particle-Accelerating Colliding-Wind Binaries with the Giant Metrewave Radio Telescope - De Becker, Michaël (2020)
Synchrotron radiation identified in the radio domain for several tens of binary systems made of massive stars provides compelling evidence that a particle acceleration process is at work in these objects, hence their Particle-Accelerating Colliding-Wind Binaries (PACWB) status. Measurements of the synchrotron radio emission allow to investigate the non-thermal physics and to derive some of their properties. Non-thermal spectra are known to increase at lower frequencies, while thermal ones increase toward higher frequencies. In this context, it is worth investigating the expectations from longer wavelengths such as those measured by the Giant Metrewave Radio Telescope in India, in complementarity with the most abundant measurements at centimetric wavelengths obtained with other radio observatories such as the VLA or ATCA.